Psychosocial Issues as a Determinant of Intimate Partner Violence among Married Adults in Ondo State - Michael, Ifeoluwa; Abisoye, Faysol (citeus, 2025)
This study examines psychosocial challenges and communication styles as predictors of domestic violence among married adults in Osun State, Nigeria. Utilizing a descriptive survey research design, the study aimed to explore the influence of psychosocial issues such as interference from in-laws, financial instability, and lack of emotional support on instances of intimate partner violence. It also investigated the role of communication styles, including assertiveness, conflict management, and relational dynamics, in mitigating or exacerbating domestic violence. A total of 400 married adults were selected using stratified random sampling from diverse demographic backgrounds. Data were collected through a validated questionnaire titled